Application of Problem-Based Learning-Audio Visual Approach to Improve Science Problem-Solving Ability of Elementary School Students - Yunita Ahmad; Syarifuddin Kune; Agustan Syamsuddin (Institut Agama Islam Negeri Palopo, 2022)
This study aims to determine the application of the Problem Based Learning-Audio Visual approach in improving science skills. The research method used is quantitative. The type of research used is a quasi-experimental design with a nonequivalent control group design. The sample in this study was fourth-grade students in one of the elementary schools in Maros Regency, amounting to 44 people. Data collection techniques used tests to determine students' science problem-solving abilities. The data collected were analyzed quantitatively using descriptive statistics and inferential statistics. The results of descriptive statistical data analysis showed that the average value of the scientific problem-solving ability of the experimental class was 88.26, and the control class was 72.38. At the same time, the results of inferential statistical data analysis showed the value of sig. On problem solving ability less than 0.05 with a t value of 10.228 greater than t table 1.681.Â This means that there is an increase in the ability to solve science problems through applying the Problem Based Learning-Audio Visual approach.